Teachers’ opinion about learning continuum in evolution based on the material complexity level - Hani' Faridah; Bambang Subali (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Evolution is one of biology topics which covers a wide range of material taught across education levels. Unfortunately, the material has not been arranged according to its complexity level and students’ development. This study aimed to collect teachers' opinions about the learning continuum of evolution material based on its complexity level. This descriptive research was conducted in Bantul and Yogyakarta Cities by distributing questionnaires. As many as 68 junior high school (JHS) teachers and 43 senior high schools (SHS) teachers were selected through convenience sampling. The data gained was analyzed using descriptive statistics to determine the mode of practitioner opinion. The results showed that the JHS teachers thought that evolutionary material had a complexity level of 3 (quite complex) to level 5 (very complicated) that could be taught in class VII & IX as well as at higher level (XII SHS). Furthermore, the SHS teachers argued that the evolution material from level 3 (quite complex) to level 4 (complex) could be taught in XII class. Further research needs to be carried out using more complete instruments with more detailed indicators.